의학교육에서의 효과적인 팀 바탕학습 운영 방안 및 기대효과 - 조아라(A-Ra Cho); 한상익(Sang-Ick Han); 윤상헌(Sang-Heon Yoon); 박주현(Joo-Hyun Park); 유남진(Nam-Jin Yoo); 김선(Sun Kim) (Korean journal of medical education, 2010)
Purpose: The aim of this study was to analyze the results of quantitative and qualitative student evaluations of team-based learning (TBL) and student achievement evaluations during TBL. Methods: Questionnaires that evaluated medical student perception and self-assessment of the TBL experience included 38questions on the TBL process. Also, we used scores from the TBL session to investigate student academic achievement. Results: Our results showed that the more proper the educational environments were, the more focused students were on team learning. According to the distribution period for preliminary assignments, there was a difference in self-directed learning. In addition,team members had the opportunity to learn new knowledge by interacting with each other, and when they had the experience of feedback, they understood the instruction topics through team learning better. With regard to peer evaluation, the students who recognized the importance of assessment studied more sincerely and honestly. By experiencing the TBL process, every team showed a high significance in the group readiness assurance test score compared with the individual readiness assurance test score, and student satisfaction with the TBL and expectation levels about capacity strengthening increased as well. Conclusion: TBL is an effective teaching and learning method and has positive impacts on student academic achievement. A study on student academic achievement and perception of TBL is expected to provide medical educators with suggestions on planning teaching strategies for effective TBL administration. KCI Citation Count: 39